Experiences Of The Cast-In-Situ Pile Filling In Stone-Line Intercalation - Guan Jichang (Deep Foundations Institute, 1991)
An abandened breakwater, located at the rear of No. 2 berth in Dongdu Port area of Xiamen City, was not cleaned thoroughly when the backfilling of sand started. The uncleaned stone layer was about 2 to 3 meters deep, with the average piece of stone weighing about 1 to 3 kN. A large grain storing house, 220X 60m2 in area, was designed and built at the above mentioned complicated site. The foundation of the grain house are made up of the cast-in-situ piles. It is well known that it is difficult for the submarine engineering drill to go down through such large-sized stones. Having com-pared the various plans, a final decision has been made which involves explosions with small amounts of charge plus cone bit in the enlarging of the size of the pores. Such a method has successfully prevented the pores from slumping and made it possible to fulfill the project without any difficulties. This paper also introduces the ways in effectively dealing with each individual stone.